Study Analysis of the Role of High-Calorie Food (Junk Food) on the Incident of Adolescent Obesity: A Community-Based Observational Study of Senior High School Adolescents in Tangerang Regency, Indonesia - Stanislas Kotska Marvel Mayello Teguh; Santoso, Alexander Halim (Community Medicine and Education Journal, 2024)
Adolescent obesity is an increasingly worrying global health problem. Consuming high-calorie foods (junk food) is thought to be one of the main risk factors. This study aims to analyze the role of high-calorie foods on the incidence of obesity in senior high school adolescents in Tangerang Regency, Indonesia. This community-based observational research involved 350 randomly selected senior high school students in Tangerang Regency. Data were collected through food questionnaires, anthropometric measurements, and biochemical examinations. Statistical analysis was performed using logistic regression to identify the association between junk food consumption and obesity, with adjustment for potential confounding factors. The results showed that consumption of high-calorie foods was significantly associated with an increased risk of obesity in adolescents (OR = 2.87; 95% CI: 1.65-4.98). Adolescents who frequently consume junk food have a 2.87 times higher risk of becoming obese than those who rarely consume it. Apart from that, a positive relationship was also found between the frequency of consumption of junk food body mass index (BMI), and waist circumference. Consumption of high-calorie foods has a significant role in increasing the risk of obesity in senior high school adolescents in Tangerang Regency. Comprehensive nutritional and public health interventions are needed to reduce junk food consumption and promote healthy eating patterns to prevent obesity in adolescents.